E-Version - Edwin Agbaike, Managing Editor: (Covenant Journal of Physical and Life Sciences, 2017)
publication may be reproduced, stored in a retrieval system or transmitted in any form or by any meams, electronic, electrostatic, magnetic tape, mechanical, photocopying, recording or